2016
DOI: 10.18632/oncotarget.9598
|View full text |Cite
|
Sign up to set email alerts
|

A key role of GARP in the immune suppressive tumor microenvironment

Abstract: In melanoma patients, one of the main reasons for tumor immune escape and therapy failure is the immunosuppressive tumor microenvironment. Herein, suppressive immune cells and inhibitory factors secreted by the tumor itself play a central role.In the present study we show that the Treg activation marker GARP (glycoprotein A repetitions predominant), known to induce peripheral tolerance in a TGF-β dependent way, is also expressed on human primary melanoma. Interestingly, membrane bound GARP is shed from the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 43 publications
(44 reference statements)
4
59
0
Order By: Relevance
“…After Fc-receptor blocking, cells were stained for surface markers in FACS buffer. Antibodies against mouse CD4 (clone RM4-5), FoxP3 (FJK-16), CD11b (M1/70), GARP (YGIC86), LAP (TW7-16B4), IgD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), IgM (eb121-15F9), CD23 (B3B4), CD86 (GL1), MHC-I (SF-1.1.1), MHC-II (M5/114.15.2), CD44 (IM7), CD62L (MEL-14), PD-L1 (B7-H1), CD1d (L363), Helios (22F6), and CD5 (53-7.3) were purchased from ThermoFisher. Anti-mouse CD8a (53-6.7), Gr1 (RB6-8C5), CD21 (7G6), CD80 (16-10A1), PD-1 (J43), Ki67 (SolA15), and pSmad (O72-670) were purchased from BD Biosciences.…”
Section: Lrrc32mentioning
confidence: 99%
See 1 more Smart Citation
“…After Fc-receptor blocking, cells were stained for surface markers in FACS buffer. Antibodies against mouse CD4 (clone RM4-5), FoxP3 (FJK-16), CD11b (M1/70), GARP (YGIC86), LAP (TW7-16B4), IgD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), IgM (eb121-15F9), CD23 (B3B4), CD86 (GL1), MHC-I (SF-1.1.1), MHC-II (M5/114.15.2), CD44 (IM7), CD62L (MEL-14), PD-L1 (B7-H1), CD1d (L363), Helios (22F6), and CD5 (53-7.3) were purchased from ThermoFisher. Anti-mouse CD8a (53-6.7), Gr1 (RB6-8C5), CD21 (7G6), CD80 (16-10A1), PD-1 (J43), Ki67 (SolA15), and pSmad (O72-670) were purchased from BD Biosciences.…”
Section: Lrrc32mentioning
confidence: 99%
“…Multiple studies in Tregs have demonstrated that GARP promotes TGF-β biogenesis and LTGF-β activation (8)(9)(10). Further, GARP expression has been observed in cells with heightened TGF-β activity: hepatic stellate cells (11), mesenchymal stromal cells (12), and multiple aggressive cancer types (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…GARP 2 is a type 1 transmembrane protein with 20 leucinerich repeats in the extracellular domain, a single transmembrane domain, and a short 14-amino acid cytoplasmic tail (1)(2)(3)(4)(5). GARP is highly expressed by platelets, activated regulatory T cells (Tregs) (6 -9), mesenchymal stromal cells (10), hepatic stellate cells (11), and transformed tumor cells (12,13). Multiple studies have established that GARP plays a role in activating TGF␤ by mediating the surface expression and integrin-mediated activation of latent TGF␤ (1, 2, 8, 14 -18).…”
mentioning
confidence: 99%
“…GARP participates in the regulatory function of activated Tregs, demonstrated by impaired suppressive activity upon GARP silencing (4,6) and inefficient support by GARP KO T cells for the generation of inducible Tregs (19). Aberrant overexpression of GARP in the tumor microenvironment also promotes Treg generation and immune escape (12,13). Recently, we further identified that gp96 plays an essential role in surface GARP-TGF␤ complex expression by chaperoning GARP in the endoplasmic reticulum (5).…”
mentioning
confidence: 99%
“…In contrast, the expression of other immunosuppressive molecules on iTregs, such as CD39, LAG3, and CTLA4 (Figure 1, I-K), was not affected by pSTAT3 inhibition. Upregulation of PD-1 and GARP in pSTAT3-inhibited iTregs was functionally relevant because neutralization of PD-1 or LAP/TGF-β1, the ligand for GARP (31,32), with monoclonal antibodies significantly impaired the suppressive function of the pSTAT3-inhibited iTregs ( Figure 1L). Conversely, inhibiting the CD39 ectonucleotidase with ARL67156 (30) had no effect on pSTAT3-inhibited iTreg potency ( Figure 1L).…”
Section: Resultsmentioning
confidence: 99%